Economic Evaluation of Short Rotation Eucalyptus Plantation Harvesting System: A Case Study - Guerra, Saulo Philipe Sebastião [UNESP]; Oguri, Guilherme; Takitane, Izabel Cristina [UNESP]; Caterina, Giulia Lembo [UNESP]; Esperancini, Maura Seiko Tsutsui [UNESP] (Springer Nature, 2017)
Recently, the New Holland Company brought to Brazil a forager machine to harvest short rotation coppice (SRC) Eucalyptus plantation focusing on high quantity of low-priced woodchips. There are other harvesting machines available on market and each harvesting system has pros and cons. Since, in general, the harvesting and chipping costs represents the main operational costs, evaluating the economic feasibility of the chosen harvesting system is crucial. Therefore, a case study was conducted to analyse the cost of this new system in Brazil that uses a modified forager harvester and a pulled-tractor silage trailer in SRC Eucalyptus plantation. The cost analysis methodology was adapted from ASABE and the costs obtained were determined in two units: cost per time and quantity harvested in oven-dry ton (odt). The system’s effective field productivity and productivity were 0.44 ha h–1 and 31.0 odt h–1, respectively. The harvest system’s total operational cost was € 258 pmh–1 or € 18.9 odt–1 and the harvester machine was the largest contributor of total cost with fixed total cost of € 87 pmh–1 and € 6.4 odt–1. In spite of high labor charges values and high exchange rates in Brazil, the total estimated cost was cheaper than the ones found in temperate countries. From the total cost, depreciation and fuel consumption were the biggest influences. Thus, the experience levels of the harvester and tractor operators are crucial to this system economy.